Arabidopsis V-ATPase activity at the tonoplast is required for efficient nutrient storage but not for sodium accumulation - Krebs, Melanie; Jawurek, Esther C.; Schumacher, Karin (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The productivity of higher plants as a major source of food and energy is linked to their ability to buffer changes in the concentrations of essential and toxic ions. Transport across the tonoplast is energized by two proton pumps, the vacuolar H+-ATPase (V-ATPase) and the vacuolar H+-pyrophosphatase (V-PPase); however, their functional relation and relative contributions to ion storage and detoxification are unclear. We have identified an Arabidopsis mutant in which energization of vacuolar transport solely relies on the activity of the V-PPase. The vha-a2 vha-a3 double mutant, which lacks the two tonoplast-localized isoforms of the membrane-integral V-ATPase subunit VHA-a, is viable but shows day-length-dependent growth retardation. Nitrate content is reduced whereas nitrate assimilation is increased in the vha-a2 vha-a3 mutant, indicating that vacuolar nitrate storage represents a major growth-limiting factor. Zinc is an essential micronutrient that is toxic at excess concentrations and is detoxified via a vacuolar Zn2+/H+-antiport system. Accordingly, the double mutant shows reduced zinc tolerance. In the same way the vacuolar Na+/H+-antiport system is assumed to be an important component of the system that removes sodium from the cytosol. Unexpectedly, salt tolerance and accumulation are not affected in the vha-a2 vha-a3 double mutant. In contrast, reduction of V-ATPase activity in the trans-Golgi network/early endosome (TGN/EE) leads to increased salt sensitivity. Taken together, our results show that during gametophyte and embryo development V-PPase activity at the tonoplast is sufficient whereas tonoplast V-ATPase activity is limiting for nutrient storage but not for sodium tolerance during vegetative and reproductive growth.